Financial vulnerability and economic dynamics in Malaysia - Tai-Hock Kuek; Chin-Hong Puah; M. Affendy Arip (Journal of Central Banking Theory and Practice, 2020)
This study attempts to develop a financial vulnerability indicator serving as a composite indicator for the state of financial vulnerability. The indicator was constructed from 10 variables of macroeconomic, financial and property market by extracting a common vulnerability component through the dynamic approximate factor model. On the feedback and amplification effects, the outcome revealed that financial vulnerability shock catalysed significant negative effects on economic activity in a high-vulnerability regime, while the impact was negligible in periods of low vulnerability. This study highlighted the usefulness of composite indicators as an early warning mechanism to gauge vulnerabilities in the Malaysian financial system.
Keywords: C11; C32; C58; E44; G01; 330; Financial Vulnerability Indicator; Financial Crises; Macro-financial Linkages; Markov-switching Bayesian VAR